2018
DOI: 10.18226/23185279.v6iss3p1
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização de aerogéis de celulose com adição de metiltrimetoxissilano (MTMS) para adsorção de petróleo

Abstract: A utilização de adsorventes é uma maneira eficaz para a remoção do óleo em terra ou água. Os aerogéis são uma classe de adsorventes, que são caracterizados pela sua estrutura altamente porosa e o seu baixo teor de sólidos, o que confere ao material uma elevada capacidade de adsorção de petróleo. No presente trabalho, foi avaliada a influência da concentração de celulose e metiltrimetoxissilano (MTMS) na capacidade de adsorção de petróleo do aerogel. Os aerogéis produzidos apresentaram baixa massa específica (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The nanofibers that make up the cell wall in a multilayer structure will thus be individualized from the pulp. 33 This method, as well as the parameters used, were cited by several authors [34][35][36][37][38] to whose reported the formation of cellulose nanofibers, with diameter ranging from 50 to 90 nm and apparent density estimated at 0.414g cm À3 , confirmed by the results of transmission electron microscopy (TEM) and Field Emission Gun -Scanning Electron Microscope (FEG-SEM) techniques.…”
Section: Methodsmentioning
confidence: 87%
“…The nanofibers that make up the cell wall in a multilayer structure will thus be individualized from the pulp. 33 This method, as well as the parameters used, were cited by several authors [34][35][36][37][38] to whose reported the formation of cellulose nanofibers, with diameter ranging from 50 to 90 nm and apparent density estimated at 0.414g cm À3 , confirmed by the results of transmission electron microscopy (TEM) and Field Emission Gun -Scanning Electron Microscope (FEG-SEM) techniques.…”
Section: Methodsmentioning
confidence: 87%